Exploring the Role of Theory of Planned Behavior on Covid-19 Vaccination Intention - Zaid Zaid; Arundati Shinta; Mahbub Pasca Al Bahy (Journal of Educational, Health and Community Psychology, 2022)
This study focuses more on identifying the role of the Theory of Planned Behavior (TPB) in predicting public intentions to get the Covid-19 vaccine in Special Region of Yogyakarta. Three hypotheses were then put forward in the form of attitude (H1). Subjective norms (H2) and perceived behavioral control have a positive and significant effect on Covid-19 vaccination intention (H3). By using a quantitative method through a cross-sectional survey approach involving 426 respondents, the results of this study ultimately concluded that Covid-19 vaccination intention was determined by attitudes towards the Covid-19 vaccine (Î² = 0.447, T-Value = 8,079, p-value = 0.000), subjective norm (Î² = 0.176, T-Value = 3.271, p-value = 0.001) and perceived behavioral control (Î² = 0.263, T-Value = 6.348, p-value 0.000). And among the three, attitudes were found to be the strongest and most significant predictor of Covid-19 vaccination intention. Several limitations and suggestions were also proposed in this research.